Human resource management as a tool for school effectiveness - Pheto, P. S. S. (University of the Free State (South Campus), 2000)
The change from apartheid to post-apartheid society in South Africa has far reaching results for the country in general and education in particular. This places great challenges to educational managers in schools, particularly in in-effective schools and the transformation of such schools. A challenge to principals, deputy principals and heads of departments is to become catalysts of change and to promote democratization of management in schools. They need to develop educators, as key organizational assets, in their schools and to promote co-operation in the management and transformation of especially in-effective schools. The aim of the study was to show how an insightful and holistic application of human resource management and development, as a sub-discipline of school management, has the potential to make dramatic, meaningful and practical contributions to the rehabilitation of in-effective schools by identifying the successful structural components of effective schools, and then applying these to ineffective schools. The methodology used comprised identifying the causes of school in-effectiveness in specific schools in the Odendaalsrus District, and then indicating how these problem areas could be resuscitated by applying similar structures which were working successfully in effective schools to these in- effective schools. The role of the principal as a human resource practitioner was investigated, while suggestions were given as to how the principal could improve the effective running of the school by: • Improving his or her knowledge and skills of human resource management by further self study, as well as using successful programmes used by other schools. • A participatory management style, where all staff members contribute to the aims and objectives of the school. • Introducing in-service training programmes, workshops and seminars for staff members. • Encouraging and promoting further study among staff members.
Dissertation (M.Ed. (Postgraduate Education))--University of the Free State, 2000
Keywords: Human resource management; School management; Principal's role; In-service training programmes